Towards developing a theoretical framework for measuring academics’ career Success in the Malaysian research universities. - Al-Mansor, Abu Said (2011)
The purpose of this article is to develop a theoretical framework for measuring career success of academics in the research universities. Theoretical explanations underpinning this study are based on social cognitive career theory and integrated proactive behaviour model. This study found five factors that have potential influences on academics‟ career success which include human capital factors, personality factors, person job-fit, personal and professional networking, and proactive behaviour. In addition, this study proposes proactive behaviour as a mediator between personality and academics‟ career success. Practical implications are in terms of strengthening the HRD framework through organizational development, training and career development that can promote positive career outcomes (objective and subjective career success).